Perbandingan Profil Lipid pada Tikus Putih yang diberi Crude Fucoidan dari Rumput Laut Coklat (Sargassum polycystum) yang Diinduksi Diet Tinggi Lemak - Juliana Irem Adriana Purukan; Kusmardi Kusmardi; Dian Ratih Laksmitawati; Syamsudin Abdillah; Bambang Ponco Priosoeryanto (Fakultas Farmasi Universitas Pancasila, 2019)
: Brown seaweed (Sargassum polycystum) is one of the plants that produces pharmacological activity which is as anti-atherosclerotic with the potential chemical content is fucoidan. The aim of this research is to know the effectiveness of crude fucoidan in decreasing total cholesterol, LDL, TG, increasing HDL levels and atherogenic index. In the optimization phase, 5 rat test animals were used to see the effect of the composition of a high-fat diet given on lipid profiles. While in the testing phase 30 test animals were divided into 6 groups to see the effect of a high-fat and crude fucoidan diet given to lipid profiles. Examination of lipid profiles was carried out three times, namely on the 0th, 14th and 36th days, after that the atherogenic index is calculated. On the 36th day the test, rats were anesthetized and necropsy for subsequent blood collection through the heart organ.The results showed that 200 mg crude fucoidan dose could significantly decreasing total cholesterol, LDL, TG, increased HDL levels and significantly decreased the atherogenic index of rat serum compared to the dosages of 100 mg and 50 mg, but did not differ significantly from the positive control at 10 mg atorvastatin.